Effects of the COVID-19 pandemic on initial treatment of malignant neoplasms of the eye and appendices in children and adolescents (Research, Society and Development, 2023)
In Brazil, the disease that most leads children and adolescents to death is cancer. In this age group, it is important to highlight neoplasms of the eyes and appendances. The pandemic caused by the Coronavirus SARS-CoV-2, in 2020, changed the operational logistics structured by the Unified Health System (SUS). In this scenario, Law 12,732/2012, which guarantees the right to start cancer treatment within 60 days of diagnosis, may have been neglected. The scope of this article was to determine the impact of the Pandemic on the applicability of Law 12,732/2012 with regard to neoplasms of the eyes and appendances in children and adolescents. This is a retrospective cross-sectional observational study, based on public data, available on the TABNETBD 1.0 platform - Oncology Panel, originating from the Ministry of Health. The selection of information took place through the variables: age group (0-19 years), detailed diagnosis (malignant neoplasms of the eyes and annexes), month/year of diagnosis (January 2019-December 2021) and time to start treatment. During the analyzed period, 493 cases were reported, 186 in 2019, 145 in 2020 and 162 in 2021. And 27 exceeded the limit stipulated by law 12,732/2012.